An investigation of the antimicrobial and antifouling properties of marine algal metabolites - Mann, Maryssa Gudrun Ailsa (Rhodes University, Faculty of Pharmacy, Pharmacy, 2008)
Prevention of the accumulation of undesirable biological material i.e. biofouling upon a solid surface requires the use of antifouling systems. The solid surface may be a contact lens, an off shore oil rig or a living organism. When chemicals are employed as a mechanism of defense against biofouling, the agents involved are known as antifouling agents. Marine algae must protect themselves from fouling organisms and it is thought that one of the mechanisms used by these organisms is the production of secondary metabolites with an array of biological activities. In vitro studies have shown numerous compounds isolated from marine algae to possess antibacterial, antifungal and antimacrofouling activity. The aim of this study was to evaluate the secondary metabolite extracts of selected Southern African marine macro-algae as a potential source of compounds that inhibit biofilm formation and that could be used as antifouling agents. In this project, marine macro-algae were collected from various sites along the South African coastline. Their extracts were screened for antimicrobial activity against four ubiquitous microorganisms, Staphylococcus aureus, Klebsiella pneumoniae, Mycobacterium aurm and Candida albicans. Results of screening assays guided the fractionation of two Rhodophyta, Plocamium corallorhiza and Laurencia flexuosa. The algae were fractionated using silica gel column chromatography and compounds were isolated by semi-preparative normal phase HPLC. Compound characterization was performed using UV, IR and advanced one- and two-dimensional NMR (¹H, ¹³C NMR, COSY, HSQC, HMBC and NOESY) spectroscopy and mass spectrometry. Ten halogenated monoterpenes including four members of the small class of halogenated monoterpene aldehydes were isolated from extracts of P. corallorhiza. The compounds isolated included the known compounds 3,4,6,7-tetrachloro-3,7-dimethyl-1-octene; 4,6-dibromo-1, 1-dichloro-3,7 -dimethyl-2E,7 octadiene; 4,8-d ibromo-1,1,7 -trichloro-3, 7-dimethyl-2,5Eoctadiene;1 ,4,8-tribromo-3, 7 -dichloro-3,7-dimethyl-1 E,5E-octadiene; 8-bremo-6, 7-dichloro-3,7-dimethyl-octa-2E,4E-dienal; 4-Bromo-8-chloro-3,7-dimethyl-octa-2E,6E-dienal; 4,6- Dibromo-3,7-dimethyl-octa-2E,7-dienal; 2,4-dichloro-1-(2-chlorovinyl)-1-methyl-5-methylidene-cyclohexane and two new metabolites 4,8-chloro-3,7-dimethyl-2Z,4,6Z-octatrien-1-al and Compound 3.47. Methodology was developed for the chemical derivatization and mass spectrometric analysis of the aldehydic compounds, The aldehyde trapping reagent 0-(2,3,4,5,6-pentafluorobenzyl)hydroxylamine hydrochloride was used to derivatize the molecules, stabilizing them and allowing for their complete characterization. From Laurencia flexuosa a new cuparene sesquiterpene 4-bremo-2-(5-hydroxy-1,2,2- trimethylcyclopent-3-enyl)-5-methylphenol was isolated along with two geometric isomers of the vinyl acetylene bromofucin , An halogenated monoterpene 3S*,4R*-1-bromo-3,4,8-trichloro-9-dichloromethyl-1-E,5-E,7-Z-octatriene was also isolated but was suspected to be a contaminant and an investigation into its biological source revealed that it originated from Plocamium suhrii. A third alga, Martensia elegans was extracted based on published reports of antimicrobial compounds in related species. A new a-alkyl malate derivative was isolated and characterized. Selected compounds isolated during the course of the study were employed in preliminary assays that tested their ability to inhibit biofilm formation by Pseudomonas aeruginosa. The halogenated monoterpenes isolated from the Plocamium species were the only active compounds. 3S*,4R*-1-bromo-3,4,S-trichloro-g-dichloromethyl-1-E,5-E,7-octatriene from P. suhrii inhibited biofilm formation through antibacterial activity on planktonic cells but could not prevent biofilm formation when employed as a film on the surface of microtitre plate wells. 1,4,8-tribromo-3,7-dichloro-3,7-dimethyl-1E,5E-octadiene and 4,6-dibromo-1,1-dichloro-3,7-dimethyl-2E,7-octadiene inhibited biofilm formation when applied as a film to the microtitre plate wells but had no significant antibacterial activity. No potential antifouling agents were identified in this project but the antimicrobial activity exhibited by the crude algal extracts was highly encouraging and a number of new research areas have been identified.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Anti-infective agents; Marine metabolites -- Therapeutic use; Marine algae; Pharmacognosy; Fouling; Marine fouling organisms